Nanocellulose-based separators in lithium-ion battery - Mathew, Manjusha Elizabeth; Ishak Ahmad,; Thomas, Sabu; Mohammad Kassim,; Rusli Daik, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Lithium-ion batteries are the essential parts of many portable electronic devices. They draw substantial recognition by virtue of their advantages over other batteries. Separators are critical to the working of lithium-ion batteries. The separator is a key component of lithium-ion battery that isolates the cathode and anode. Though the separator does not participate in the electrochemical process, it plays a major role in the safety of the battery. Nanomaterials are used in many applications in our life. Nanocellulose are sustainable materials used to fabricate parts of energy storage devices. This review discusses the potential of nanocellulose incorporated materials to use as separators in lithium-ion batteries.